2016
DOI: 10.1017/s1473550416000173
|View full text |Cite
|
Sign up to set email alerts
|

Biochip-based instruments development for space exploration: influence of the antibody immobilization process on the biochip resistance to freeze-drying, temperature shifts and cosmic radiations

Abstract: International audienceDue to the diversity of antibody (Ab)-based biochips chemistries available and the little knowledge about biochips resistance to space constraints, immobilization of Abs on the surface of the biochips dedicated to Solar System exploration is challenging. In the present paper, we have developed ten different biochip models including covalent or affinity immobilization with full-length Abs or Ab fragments. Ab immobilizations were carried out in oriented/non-oriented manner using commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Indeed, it was demonstrated that DGLs are readily soluble in water at least up to 60 gL À1 in water, [12] are stable under sterilization conditions, [28] and are partially degradable under the action of endogenous peptidases. Indeed, it was demonstrated that DGLs are readily soluble in water at least up to 60 gL À1 in water, [12] are stable under sterilization conditions, [28] and are partially degradable under the action of endogenous peptidases.…”
Section: Biology Biocompatibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it was demonstrated that DGLs are readily soluble in water at least up to 60 gL À1 in water, [12] are stable under sterilization conditions, [28] and are partially degradable under the action of endogenous peptidases. Indeed, it was demonstrated that DGLs are readily soluble in water at least up to 60 gL À1 in water, [12] are stable under sterilization conditions, [28] and are partially degradable under the action of endogenous peptidases.…”
Section: Biology Biocompatibilitymentioning
confidence: 99%
“…In order to enter the real world of industrial applications,s uch as drug and gene delivery,b iomaterial and tissue engineering, bioimaging or biosensing, polymers should display an umber of crucial propertiest hat we believe DGLs exhibit. Indeed, it was demonstrated that DGLs are readily soluble in water at least up to 60 gL À1 in water, [12] are stable under sterilization conditions, [28] and are partially degradable under the action of endogenous peptidases. [29] In addition, these biomacromolecules are non-immunogenic [30] and carry low cytotoxicity (i.e., IC50 values on Hep2 cellso f1 6.8, 13.2, and 13.9 mgmL À1 from second-to fourth-generation DGL, respectively), [31] in comparison with other polycationic polymers (e.g.,a bout 90 %v iability for DGL G3 versusl ess than 50 %v iability for hyperbranched PEI at as ame concentration of 12.5 mgmL À1 on HeLa cells).…”
Section: Biology Biocompatibilitymentioning
confidence: 99%
“…Thus, the very polymers that are indicative of life are rendered undetectable with GC-MS (Poinot and Geffroy-Rodier, 2015). Other analytical strategies proposed for space missions include biosensors (Coussot et al ., 2017) and antibody-based systems such as the Life Marker Chip (Rix et al ., 2011). However, these approaches lack flexibility as the instruments must be built with specific molecular targets.…”
Section: Introductionmentioning
confidence: 99%
“…One main concern relies on the resistance of biochips to the cumulative effects of these radiations. In recent years, studies have been performed to evaluate the resistance of antibody reagents to space constraints, especially regarding the effect of specific particles on antibody binding performances (Le Postollec et al, 2009a;Le Postollec et al, 2009b;Baqué et al, 2011a;de Diego-Castilla et al, 2011;Baqué et al, 2017;. To complement ground-based radiation studies, a short term mission was performed on the BIOPAN-6 low-earth orbit platform to demonstrate the effects of cumulative radiations on the antibodies' ability to bind to their respective antigens (Derveni et al, 2012;Derveni et al, 2013).…”
Section: Introductionmentioning
confidence: 99%